1988
DOI: 10.1083/jcb.107.6.2757
|View full text |Cite
|
Sign up to set email alerts
|

Induction of tenascin in healing wounds.

Abstract: Abstract. The distribution of the extracellular matrix glycoprotein, tenascin, in normal skin and healing skin wounds in rats, has been investigated by immunohistochemistry. In normal skin, tenascin was sparsely distributed, predominantly in association with basement membranes. In wounds, there was a marked increase in the expression of tenascin at the wound edge in all levels of the skin. There was also particularly strong tenascin staining at the dermal-epidermal junction beneath migrating, proliferating epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
338
2
3

Year Published

1994
1994
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 509 publications
(358 citation statements)
references
References 25 publications
15
338
2
3
Order By: Relevance
“…Tenascin-C is highly expressed during tissue remodeling and repair (Jones and Jones, 2000;ChiquetEhrismann and Chiquet, 2003). Deposition of tenascin-C is markedly increased at the wound edges, particularly at the dermal-epidermal junction (Mackie et al, 1988). Its modulatory effects on cell adhesion suggest a role in promoting epidermal cell migration and proliferation.…”
Section: Discussionmentioning
confidence: 90%
“…Tenascin-C is highly expressed during tissue remodeling and repair (Jones and Jones, 2000;ChiquetEhrismann and Chiquet, 2003). Deposition of tenascin-C is markedly increased at the wound edges, particularly at the dermal-epidermal junction (Mackie et al, 1988). Its modulatory effects on cell adhesion suggest a role in promoting epidermal cell migration and proliferation.…”
Section: Discussionmentioning
confidence: 90%
“…Our findings are thus in line with the report of tenascin-C involvement in myofibroblast recruitment [26]; the presence of tenascin-C on day 50 postirradiation in our study signals immature tissue granulation and on-going migration. MSC and GF treatment thus appear to have accelerated the wound healing process, with tenascin-C rapidly disappearing after wound contraction was complete [33]. The a-SMA + myofibroblasts are present in the early stage of the wound, and they rapidly disappear when wound healing progresses [34].…”
Section: Figmentioning
confidence: 98%
“…In the mice treated by MSCs and GFs, real-time PCR analysis showed that tenascin-C expression remained high compared to nonirradiated mice, but immunostaining revealed discontinuous localization in the dermal-epidermal junction, mostly close to hair follicles. Some reports indicate that tenascin-C is present throughout the matrix of granulation tissue, filling full-thickness wounds, but it is not detectable in the scar after the completion of wound contraction [33]. Tenascin-C may also interact with the contractile properties of myofibroblasts to influence wound contraction.…”
Section: Figmentioning
confidence: 99%
“…The genes of focus in these studies are tenascin-C and collagen fibril-associated type XII collagen. Tenascin-C, which is not normally expressed in adults, changes its expression patterns during embryogenesis and regenerative processes and appears under pathological conditions and adjacent to contracting wounds (Mackie et al, 1988;Silver et al, 2003). Tensile loading has been shown to control tenascin-C mRNA expression in chicken skin fibroblasts.…”
Section: Regulation Of Gene Expression In Fibroblasts By Mechanical Lmentioning
confidence: 99%